APPLICATION OF IFRS WITH DISCLOSURE OF FIXED ASSETS IN THE COMPANY'S FINANCIAL STATEMENTS - Nonon Dherian Rizky; Wawan Asad Sutrisna (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2023)
The aim of this research is to analyze the implementation of IFRS and its relationship with the comparison of disclosure of fixed assets or now called PPE (Property, Plant, and Equipment) in financial reports. The variable used in this research is the application of IFRS which focuses on the comparison of PPE disclosures. This research is based on previous research conducted by Vergauwe and Gaeremynck (2013). The sample for this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022. Data was collected using a purposive sampling method, observations were analyzed. Hypothesis testing in this research uses regression analysis Based on the results of the regression test, the application of IFRS does not have a significant effect on the disclosure of fixed assets in financial statements.